Atomic scale engineering and understanding of novel interfaces between oxide films and semiconductor crystals - Yasir, Muhammad (fi=Turun yliopisto|en=University of Turku|, 2017)
Surface properties of semiconductor crystals play a significant role in the operation of different devices like transistors, LEDs, and solar cells. For better performance of the devices, it is essential to minimize the amount of harmful surface and interface defects. For example, control over the oxygen induced defects is difficult during deposition of any film (e.g., metal oxide films) on a semiconductor crystal. On the other hand, tailoring and characterization of the semiconductor interfaces is not an easy task due to the buried nature of these structures. In this thesis, we have studied the effect of different adsorbates (Sr, Ba, Si, and Sb) and metal oxides (BaO, SiO2, Al2O3 and Sb2O3) on different semiconductor surfaces: Si(100), Ge(100) and GaAs(100). In this experimental work, several complementary characterization methods were used including low energy electron diffraction (LEED), synchrotron-radiation photoemission spectroscopy (SR- PES) and scanning tunneling microscopy (STM). These results were interconnected to capacitance-voltage (CV) and photoluminescence (PL) measurements via collaboration with other research groups. The results can be summarized as follows: It is demonstrated the reduction in the defects amount at Al2O3/GaAs interface when an intermediate thin layer of BaO was deposited before atomic layer deposition of Al2O3. In the case of epitaxial BaO/SiO2 system, the crystallinity of the interface even after the incorporation of significant amount of oxygen atoms into Si is an interesting finding. It is also evident in this research that metal interaction with semiconductor substrate can also induce degradation in the interface. This degradation can be avoided with the modification of starting surface and by adopting a specific procedure for oxide film growth. Furthermore, a growth of crystalline Sb2O3 film has been also presented by careful consideration of deposition temperature and time.

Kiteisten puolijohdepintojen ominaisuudet vaikuttavat merkittävästi erilaisten laitteiden kuten transistoreiden, LED:ien ja aurinkokennojen toimintaan. Olennainen osa näiden laitteiden tehokkuuden parantamista on erilaisten haitallisten pinta- ja rajapintavirheiden minimointi. Esimerkiksi hapen aiheuttamia virheitä on vaikea kontrolloida kasvatettaessa mitätahansa ohutkalvoa (esim. metallioksidikalvot) kiteisen puolijohteen päälle. Toisaalta puolijohderajapinnat ovat luonteensa takia hankalia mallintaa ja karakterisoida, koska ne pinnan alla (hautautuneita). Tässä väitöskirjassa olemme tutkineet miten eri absorbaatit (Sr, Ba, Si ja Sb) ja metallioksidit (BaO, SiO2, Al2O3 ja Sb2O3) reagoivat erilaisilla puolijohdepinnoilla: Si(100), Ge(100) ja GaAs(100). Tässä kokeellisessa teoksessa yhdistettiin useita karakterisointimenetelmiä mukaanlukien matalaenergisten elektronien diffraktio (LEED), synkrotronifotoelektronispektroskopia (SR- PES) ja tunnelointimikroskopia (STM). Näistä mittausmenetelmistä saadut tulokset yhdistettiin kapasitanssi-jännite (CV) ja fotoluminesenssi (PL) mittauksiin, jotka suoritettiin yhteistyössä muiden tutkimusryhmien kanssa. Tutkimuksemme tulokset voidaan tiivistää seuraavasti: Haitallisten virheiden määrää voidaan vähentää Al2O3/GaAs rajapinnalla lisäämällä ohut kalvo bariumoksidia (BaO) substraatin päälle ennen alumiinioksidin atomikerroskasvatuksta. Järjestäytyneen BaO/SiO2 -systeemin tapauksessa on mielenkiintoista huomata, että rajapinta on kiteinen, vaikka pii sisälsi huomattavan määrän happiatomeja. Tässä tutkimuksessa on myös osoitettu, että metallin ja puolijohteisen substraatin vuorovaikutuksen seurauksena tapahtuu rajapinnan laadullista heikkenemistä. Tätä rappeutumista voidaan välttää muokkaamalla substraatin pintaa ja ottamalla käyttöön tietynlainen menetelmä oksidikalvon kasvatuksessa. Tämän lisäksi kiteisen Sb2O3 kalvon kasvatustapa on myös esitelty kiinnittämällä suurta huomiota kasvatuslämpötilaan ja -aikaan.